Adaption of vastii muscles in top racers from different alpine skiing disciplines - Lesnik, B.; Simunic, B.; Zvan, M.; Pisot, R. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: With the development of skiing disciplines professional alpine skiing has reached the degree, where top results are very hard to reach. In the process of training there is a mosaic of special elements for each discipline in alpine skiing. The purpose of our work was to investigate on different adaptations of skeletal muscles vastus lateralis (VL) and vastus medialis (VM) contractile properties between two groups of world cup racers: giant slalom and slalom racers (GS&SR) vs. super G and downhill racers (SG&DR).